Molecular Docking Studies of Phoenix dactylifera L. Against SARS-CoV-2 ACE-2 Receptor - Warnasih, Siti; Mulyati, Ade Heri; Kholisoh, Siti (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2022)
Dates (Phoenix dactylifera L.) are one of the most useful plants. According to previous research, those dates contain bioactive compounds with antioxidant, antimicrobial, and anti-inflammatory properties. Furthermore, dates can be used as an antiviral, but the potential of dates as an antiviral, particularly the SARS-CoV-2 antiviral, has received little attention. As a result, the goal of this study was to see if date palm bioactive compounds could be used as SARS-CoV-2 antivirals with molecular docking against the Angiotensin-Converting Enzyme-2 (ACE-2) receptor. The study was carried out using molecular docking methods with Autodock Vina, where 21 chemical compounds found in date palms as ligands were attached to the ACE-2 receptor, and four chemical compounds used as SARS-CoV-2 antiviral medicines, namely chloroquine, favipiravir, plitidepsin, and remdesivir, were used as a control ligand. The results showed that proanthocyanidin B1, B2, and quercetin ligands had the highest interaction and stability with Gibbs free energy values of -9.20 kcal/mol, -9.10 kcal/mol, and -8.20 kcal/mol, respectively. This value is known to be higher than control ligands plitidepsin -9.02 kcal/mol, remdesivir -7.88 kcal/mol, chloroquine -5.65 kcal/mol, and favipiravir -5.38 kcal/mol. As a result, dates can be used as a SARS-CoV-2 antiviral candidate.